2019
DOI: 10.1017/s0144686x19000734
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline and distinction: a new line of fracture in later life?

Abstract: Cognitive decline and dementia have become major concerns for many individuals reaching later life within contemporary Western societies. This fear of decline is central to the social divide between the third age embodying ideals of maintained health, activity and lifestyle choices, and the fourth age, a social imaginary encompassing the irreversible decline associated with ageing. In this article, we explore how brain-training technologies have become successful by relying on tensions between the third and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…We have previously described how living with memory problems without dementia may be conceptualised as liminal, between dementia and wellness, and that individuals may experience the burden of responsibility for managing dementia risk, without access to the help that may follow a definitive diagnosis ( Poppe et al, 2020 ). Libert et al (2019) explore individualistic attitudes around dementia prevention. He suggests that adopting lifestyle change for dementia prevention can be viewed as an emotional, as well as practical response to fear of dementia: as emotional distancing from dementia, a condition associated with ‘ageing without agency’.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described how living with memory problems without dementia may be conceptualised as liminal, between dementia and wellness, and that individuals may experience the burden of responsibility for managing dementia risk, without access to the help that may follow a definitive diagnosis ( Poppe et al, 2020 ). Libert et al (2019) explore individualistic attitudes around dementia prevention. He suggests that adopting lifestyle change for dementia prevention can be viewed as an emotional, as well as practical response to fear of dementia: as emotional distancing from dementia, a condition associated with ‘ageing without agency’.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on the malleable nature of the process of growing old and self-care (lifestyle) practices as the expression of responsibility for one's own ageing also impacts the perception of dementia as the symbol of the fourth age. Libert et al (2020) discussed the emergence of active cognitive ageing concerning the expansion of the brain-training discourse that highlights the role of risk-management practices in preventing dementia. Cognitive decline is no longer viewed as irreversible and inevitable.…”
Section: New Fractures In Later Life Expanding the Range Of 'Abnormal...mentioning
confidence: 99%
“…For example, Lawless et al (2018), in their analysis of the website of a non-profit dementia organisation, revealed that everyone is positioned as at-risk of developing dementia, and lifestyle choices and practices (such as brain training) are presented as responsible, appropriate and necessary responses to this fact. Libert et al (2020Libert et al ( , p. 2585) stated that engagement in those practices allows older people to demonstrate to themselves and others their cognitive health and position themselves away from dementia and the imaginary of 'failed' ageing as the active and responsible 'third agers. '…”
Section: New Fractures In Later Life Expanding the Range Of 'Abnormal...mentioning
confidence: 99%
See 2 more Smart Citations